THE URGENCE OF DIGITAL TECHNOLOGY IN IMPLEMENTING BK NEED ASSESSMENTS IN SCHOOL - Yenni Elfira; A. Muri Yusuf; Daharnis Daharnis (Universitas Trunojoyo Madura, 2022)
The Guidance and Counseling Program in Schools is structured based on an assessment to find logical, relevant, systematic, and quality conditions that will be used as the basis for planning guidance and counseling programs. However, the reality in the field is that there are many problems experienced by BK teachers in the implementation of BK assessments, both from the administrative process, processing and application of the results of the BK assessment. Digital technology is one solution in implementing an effective and efficient BK assessment need. Therefore, in accordance with developments, it is expected that BK teachers can be more creative in designing various BK assessment processing applications, so that the implementation of the BK program is felt to be of higher quality.